2007
DOI: 10.1111/j.1547-5069.2007.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving Participant Comprehension in the Informed Consent Process

Abstract: Despite increasing regulatory scrutiny, deficiencies still exist in participant comprehension of the research in which they participate, as well as differences in how comprehension is measured and assessed. No single intervention was identified as consistently successful for improving participant comprehension, and results indicated that any successful consent process should at a minimum include various communication modes and is likely to require one-to-one interaction with someone knowledgeable about the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 37 publications
(42 reference statements)
3
69
0
4
Order By: Relevance
“…Our findings revealed an average comprehension score of 58, indicating that some participants gave their consent without fully understanding the study protocol and risks. Similarly, in a systematic review, Cohen and Larson 12 suggested that despite increasing regulatory scrutiny, deficiencies still exist in participants' comprehension of the research in which they participate. In our study, we found a strong correlation between educational levels and subjects' average comprehension score.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings revealed an average comprehension score of 58, indicating that some participants gave their consent without fully understanding the study protocol and risks. Similarly, in a systematic review, Cohen and Larson 12 suggested that despite increasing regulatory scrutiny, deficiencies still exist in participants' comprehension of the research in which they participate. In our study, we found a strong correlation between educational levels and subjects' average comprehension score.…”
Section: Discussionmentioning
confidence: 99%
“…Bu sürecin mekanizmaları genellikle hemşirenin onam formu üzerinde hastanın imzasını almasını gerektirse de, hemşire-nin birincil önceliği otonom karar verme süreci için gerekli olan tüm ölçütlerin karşılanmasını sağ-lamaktır. 5,22,23 Hemşirelerin aydınlatılmış onam süreçlerinde yaşadığı diğer bir sorun ise hastalara doktoru tarafından aydınlatılmış onam formu imzalatılırken hemşirelerin tanık olarak bulunması ve formu imzalamalarıdır. Hemşirelerin tanık olarak formu imzalaması birtakım sorumluluğu da beraberinde getirmektedir.…”
Section: Gönüllü Onam Olmalıdırunclassified
“…10) Herhangi bir sağlık hizmeti sunarken hasta ile birlikte tartışarak, işlemlerin kaydedilmesi gerekmektedir. 6,20,22 Sullivan'a göre hemşirenin imzası; hastanın onamı isteyerek verdiğine, imzayı zamanında attı-ğına, hastanın imza atacak yeterlilikte olduğuna ve hastanın imzasının gerçek olduğuna dair beyanı-dır. 24 Tedavinin hastaya açıklandığı zamana tanık olmayan hemşireler, hastanın işlemi anlayıp anlamadığı, hekim ile görüşülmesi gereken herhangi bir sorun olup olmadığı ve hastanın baskı altında olup olmadığı konusunda bilgi edinmelidirler.…”
Section: Gönüllü Onam Olmalıdırunclassified
“…Any successful consent process should at a minimum include various communication modes and is likely to require one-to-one interaction with someone knowledgeable about the study." 52 Others have also noted instances where, even when a consent process met regulatory requirements, "it was inappropriate for most patients." 53 Fundamental issues include literacy rates in the United States of half the population at the 8th-grade level.…”
Section: Do We Achieve Informed Consent?mentioning
confidence: 99%